2018
DOI: 10.3892/mmr.2018.9734
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of the lncRNA‑miRNA‑mRNA network based on competitive endogenous RNA reveals functional genes in heart failure

Abstract: Heart failure (HF) is a principal cause of morbidity and mortality worldwide, affecting an estimated 38 million people. Although significant progress has been made with respect to the underlying molecular mechanisms, the role of the competing endogenous RNA (ceRNA) network in the pathogenesis of HF remains largely unknown. In this study, an HF-associated ceRNA network was constructed based on the differentially expressed long noncoding RNAs (lncRNAs), microRNAs (miRNAs) and mRNAs obtained, respectively, from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Moreover, the previously conducted study by Su et al also revealed highly expressed TUG1 in H 2 O 2 ‐induced cardiomyocytes, which resulted in accelerated cell apoptosis and oxidative stress 25 . In contrast, it has also been previously reported that heart failure causes a significant downregulation of TUG1 in human blood 26 . In the current study, TUG1 expression was measured in cardiomyocytes of MIRI mouse models and H/R‐induced cardiomyocyte models.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Moreover, the previously conducted study by Su et al also revealed highly expressed TUG1 in H 2 O 2 ‐induced cardiomyocytes, which resulted in accelerated cell apoptosis and oxidative stress 25 . In contrast, it has also been previously reported that heart failure causes a significant downregulation of TUG1 in human blood 26 . In the current study, TUG1 expression was measured in cardiomyocytes of MIRI mouse models and H/R‐induced cardiomyocyte models.…”
Section: Discussionmentioning
confidence: 44%
“…25 In contrast, it has also been previously reported that heart failure causes a significant downregulation of TUG1 in human blood. 26 In the current study, TUG1 expression was measured in cardiomyocytes of MIRI mouse models and H/R-induced cardiomyocyte models. These may be the reason of different expressions of TUG1 detected.…”
Section: Discussionmentioning
confidence: 94%
“…HF is the nal stage of various heart diseases, especially ICM and DCM, with high mortality and morbidity worldwide [25,26]. Although numerous studies have suggested the possible mechanisms of HF, they remain largely unknown and need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, tremendous effects have been made toward the elucidation of molecular mechanisms underlying various CVDs (Uchida and Dimmeler, 2015 ; Li S. et al, 2018 ). For example, expression of long non-coding RNAs (lncRNAs) has been detected under normal physiological conditions and in disease states, some lncRNAs are found to regulate acute myocardial infarction (such as Novlnc6) (Uchida and Dimmeler, 2015 ) and acute heart failure [such as Mhrt (Zhang et al, 2019 ), H19 (Greco et al, 2016 ), and growth arrest specific 5 (Wang G. et al, 2019 )], and gene transcripts such as MALAT1 and Tie-1-AS are found to control the growth and functions of blood vessels (Uchida and Dimmeler, 2015 ). Recently, Spinraza (a novel antisense oligonucleotide therapy) is approved by FDA to treat spinal muscular atrophy resulted from pseudogene SMN2, in which the antisense oligonucleotide is used to increase SMN2 exon 7 inclusion, thus increasing levels of survival motor neuron (SMN) protein (Chiriboga, 2017 ; Paton, 2017 ; Berciano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%